Bilingual Booklets as a Learning Introduction Media to Natural Disaster Mitigation in Wetlands - Muhsinah Annisa; Fadhlan Muchlas Abrori; Teguh Prasetio; Herti Prastitasari; Mahmuddin; Rianty Yulandra (Postgraduate, University of Mataram, 2025)
This study aims to design and evaluate the effectiveness of a bilingual booklet (Indonesian and Banjarese) as a learning media for disaster mitigation in wetland areas of South Kalimantan. The research method used is Design-Based Research (DBR) with four main stages: problem identification, product development, product testing, and reflection. The study involved 50 elementary school students selected using purposive sampling. Data was collected through validation instruments by content, media, and language experts, as well as questionnaires for teacher and student responses. The results showed that the booklet achieved validation scores ranging from 80-100% and received positive responses from both students and teachers, with scores between 95.31%-100%. The booklet implementation in two phases showed an improvement in students' cognitive and affective understanding, analyzed using paired t-tests. The conclusion of this study is that the bilingual booklet is effective in enhancing students' knowledge of disaster mitigation, with practical implications for the development of disaster education media in disaster-prone areas.